From student feedback to institutional quality enhancement initiatives that focus on supporting staff and students - Santhanam, Elizabeth; Ashford-Rowe, Kevin; Murphy, Pauline (Critical Studies in Teaching and Learning, 2023)
The broader challenges posed for teaching quality enhancement through educational and academic development are many and include: information collection to identify possible reasons for a particular set of circumstances, planning and implementation of changes in a generally fluid situation, collection of evidence for outcomes, and provision of succinct reports to stakeholders. One common means for identifying both the needs and the outcomes is through surveys. In this respect, students views on the learning and teaching environment provided by an institution are typically collected through standardised questionnaires, though the use of such survey results has been frequently debated. This paper outlines the use of information collected through surveys of student views in order to better understand student learning experiences and to identify areas for further development. It also describes specific projects and programs that were aimed at caring for both staff and students in an institution with a strong commitment to the dignity of the human person and the common good. It is noted that in addition to policies and procedures that enshrine caring and ethical behaviour among staff and students, the institution actively promotes this culture through various practices.